2002
DOI: 10.1523/jneurosci.22-23-10163.2002
|View full text |Cite
|
Sign up to set email alerts
|

Small Conductance Ca2+-Activated K+Channels Modulate Synaptic Plasticity and Memory Encoding

Abstract: Activity-dependent changes in neuronal excitability and synaptic strength are thought to underlie memory encoding. In hippocampal CA1 neurons, small conductance Ca 2ϩ -activated K ϩ (SK) channels contribute to the afterhyperpolarization, affecting neuronal excitability. In the present study, we examined the effect of apamin-sensitive SK channels on the induction of hippocampal synaptic plasticity in response to a range of stimulation frequencies. In addition, the role of apamin-sensitive SK channels on hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
236
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(260 citation statements)
references
References 68 publications
18
236
1
5
Order By: Relevance
“…For example, the decrease in SK channel function following CIE treatment observed in many regions including the OFC would be expected to enhance synaptic efficacy and plasticity. In support of this, results from previous studies show that blocking these channels facilitates LTP and enhances learning and memory (Blank et al, 2003;Brennan et al, 2008;Hammond et al, 2006;Stackman et al, 2002), whereas overexpression of SK channels reduces LTP and impairs hippocampus-, amygdala-, and mPFC-dependent learning tasks. In addition to changes in glutamate receptor expression and function described above, alterations in dendritic Figure 8 Chronic intermittent ethanol (CIE) exposure suppresses the ability of the GlyT1 transport inhibitor sarcosine to reduce spiking in lateral orbitofrontal cortex (lOFC) neurons.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 57%
“…For example, the decrease in SK channel function following CIE treatment observed in many regions including the OFC would be expected to enhance synaptic efficacy and plasticity. In support of this, results from previous studies show that blocking these channels facilitates LTP and enhances learning and memory (Blank et al, 2003;Brennan et al, 2008;Hammond et al, 2006;Stackman et al, 2002), whereas overexpression of SK channels reduces LTP and impairs hippocampus-, amygdala-, and mPFC-dependent learning tasks. In addition to changes in glutamate receptor expression and function described above, alterations in dendritic Figure 8 Chronic intermittent ethanol (CIE) exposure suppresses the ability of the GlyT1 transport inhibitor sarcosine to reduce spiking in lateral orbitofrontal cortex (lOFC) neurons.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 57%
“…The results also reinforce a previous conclusion that plasticity of the basal dendritic synapses is significantly different than that in their apical counterparts. Earlier studies had shown that LTP has a lower threshold (requires fewer theta bursts) and is greater in magnitude in the basal than in the apical dendrites in field CA1 (Arai et al, 1994;Roth and Leung, 1995;Leung and Shen, 1999), an effect that can probably be attributed to regional differences in the incidence of potassium channels that mediate the after-hyperpolarizing potentials (AHPs) initiated by individual theta bursts (Arai and Lynch, 1992;Arai et al, 1994;Sah and Bekkers, 1996;Stackman et al, 2002). LTP also differs between the two dendritic domains with regard to the degree to which it stabilizes.…”
Section: Loss Of Synaptic Plasticity In Early Middle Agementioning
confidence: 99%
“…In various neurons, SK channels influence somatic excitability by contributing to afterhyperpolarization (Stocker et al, 1999;Abel et al, 2004), modulate synaptic plasticity by coupling to NMDA receptors (Stackman et al, 2002;Faber et al, 2005;Ngo-Anh et al, 2005), and influence dendritic Ca 2ϩ levels (Cai et al, 2004). By exerting a repolarizing conductance in response to increased intracellular Ca 2ϩ , SK channels effectively form a Ca 2ϩ -mediated feedback loop with their Ca 2ϩ sources.…”
Section: Introductionmentioning
confidence: 99%